High-performance biofuel cell made with hydrophilic ordered mesoporous carbon as electrode material - Guo, Chun Xian (2013)
A highly hydrophilic ordered mesoporous carbon has been synthesized by a microwave assisted method from a mixture containing glucose and poly(vinyl alcohol) and with a silica template to have high hydrophilicity, low charge transfer resistance and large specific surface area. The new carbon material is further used as an electrode material to fabricate an anode-limited glucose/O2 biofuel cell, which gives an output power density of 110 μW cm−2 with cell voltage of 0.72 V, a performance much higher than the reported anodes made from SWNT, bi-polymer layer and carbon black at the same or even higher glucose concentration. This work provides a universal approach to synthesize functional carbon nanomaterials with desired architectures and properties for various important applications in energy conversion systems such as fuel cells and solar cells.